2021
DOI: 10.1007/s40201-021-00618-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of E. coli and Vibrio cholerae in ballast water of commercial ships: a primary study along the Persian Gulf

Abstract: Purpose Ballast water is one of the most important ways for the transfer of aquatic organisms such as Escherichia coli (E. coli) and Vibrio cholerae. The aim of this study was to investigate Mdh gene of E. coli and the OmpW gene of Vibrio cholerae bacteria by PCR technique in the ballast water of commercial ships entering Bushehr port along the Persian Gulf. Methods In this study, 34 samples of ballast water entered Bushehr port were studied by using culture and PCR methods to determine Mdh gene of E. coli and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…coli and V . cholerae excellent for controlled experiments, these species can be found in natural environments together: for example, residing in brackish water [ 32 , 33 ] and within surface-fouling biofilms in coastal waters near human populations [ 34 ]. Members of the Escherichia and Vibrio genera are also common components of zebrafish microbiota [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…coli and V . cholerae excellent for controlled experiments, these species can be found in natural environments together: for example, residing in brackish water [ 32 , 33 ] and within surface-fouling biofilms in coastal waters near human populations [ 34 ]. Members of the Escherichia and Vibrio genera are also common components of zebrafish microbiota [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our model system comprises dual-culture biofilms of Escherichia coli and Vibrio cholerae under exposure to T7 phages or λ phages. Beyond the experimental tractability that makes E. coli and V. cholerae excellent for controlled experiments, these species can be found in natural environments together: for example, residing in brackish water (32,33) and within surface-fouling biofilms in coastal waters near human populations (34). Members of the Escherichia and Vibrio genera are also common components of zebrafish microbiota (35,36).…”
Section: Introductionmentioning
confidence: 99%
“…This aroused great interest among scientists, which resulted in many works focused on ballast microbiota. A very interesting example of such scientific works is the manuscript written by Soleimani et al [ 14 ]. The authors of this work indicated that ballast waters are a very important element in the transmission of Escherichia coli and Vibrio cholerae bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated the presence of pathogenic microflora in ballast waters. It also indicated PCR assays as an appropriate alternative to conventional culture methods, which provide quick and accurate data for human health protection procedures [ 14 ]. Additionally, the presence of high levels of metabolites and organic matter in the water of ballast tanks create favorable conditions for the development of opportunistic bacteria groups, which leads to a reduction in microbiological competition within these closed spaces [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation